Methods of Teaching Sewing Terms in English and Uzbek Languages - Azizova, Fotima; Irgasheva, Dildora; Khaydarova, Saodat; Kurbanbayeva, Dilnoza; Abramova, Navbakhor (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with issues related to the basic concepts of competence and the competence approach. The notion of “professional competence” is considered as a set of knowledge and skills that determine the effectiveness of work; the scope of skills in the task; a combination of personal qualities and properties; a complex of knowledge and professionally significant personal knowledge; a vector of professionalization; and unity of theoretical and practical readiness for work. The purpose of the article is to reveal the levels of competence of students on the criteria for assessing the competence of the future designer of garments.